2022
DOI: 10.3390/genes13020211
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-Mediated Priming of Macrophage M1 Differentiation Differs in Gram-Positive and Gram-Negative Settings

Abstract: A proper regulation of macrophage polarization is essential for the organism’s health and pathogen control. Differentiation control is known to occur at the transcriptional as well as the posttranscriptional levels. The mechanisms involved, however, have not yet been fully elucidated. In this study, we co-cultured macrophages with viable Gram-positive and Gram-negative bacteria to mimic macrophage differentiation to the M1-like type in an inflammatory milieu. We found that Gram-positive stimulation resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…We observed that Akt1 mRNA levels are downregulated following TLR4 or TLR2 stimulation [94]. This is in line with the description of Akt1 as a target gene of the miRNA miR-155-5p [66,97], whose expression has been consistently reported to be upregulated by various members of the TLR family [4,5,7,11,12,20,24,25,34,42,47,58,[70][71][72][73]83,[90][91][92][98][99][100][101][102][103]. In addition, Akt1 activity is subject to post-transcriptional modulation.…”
Section: Macrophage Polarization Influenced By Mirnassupporting
confidence: 89%
See 4 more Smart Citations
“…We observed that Akt1 mRNA levels are downregulated following TLR4 or TLR2 stimulation [94]. This is in line with the description of Akt1 as a target gene of the miRNA miR-155-5p [66,97], whose expression has been consistently reported to be upregulated by various members of the TLR family [4,5,7,11,12,20,24,25,34,42,47,58,[70][71][72][73]83,[90][91][92][98][99][100][101][102][103]. In addition, Akt1 activity is subject to post-transcriptional modulation.…”
Section: Macrophage Polarization Influenced By Mirnassupporting
confidence: 89%
“…It has been described that TRAF6 is ubiquitinated and proteosomally degraded in an IRAK1-dependent manner in the context of negative feedback [28]. In addition, our own studies show a downregulation of TRAF6 mRNA levels after TLR4 or TLR2 stimulation, which is accompanied by an upregulation of the miRNA miR-351-5p [66,94]. TRAF6 has been described as a target gene of miR-351-5p [95].…”
Section: Macrophage Polarization Influenced By Mirnassupporting
confidence: 59%
See 3 more Smart Citations